Comparative analyses of salivary proteins from three aphid species. Issue 1 (1st November 2013) - Vandermoten, S.; Harmel, N.; Mazzucchelli, G.; De Pauw, E.; Haubruge, E.; Francis, F.
Abstract Saliva is a critical biochemical interface between aphids and their host plants; however, the biochemical nature and physiological functions of aphid saliva proteins are not fully elucidated. In this study we used a multidisciplinary proteomics approach combining liquid chromatography‐electrospray ionization tandem mass spectrometry and two‐dimensional differential in‐gel electrophoresis/matrix‐assisted laser desorption/ionization time‐of‐flight/mass spectrometry to compare the salivary proteins from three aphid species including Acyrthosiphon pisum, Megoura viciae and Myzus persicae. Comparative analyses revealed variability among aphid salivary proteomes. Among the proteins that varied, 22% were related to DNA‐binding, 19% were related to GTP‐binding, and 19% had oxidoreductase activity. In addition, we identified a peroxiredoxin enzyme and an ATP‐binding protein that may be involved in the modulation of plant defences. Knowledge of salivary components and how they vary among aphid species may reveal how aphids target plant processes and how the aphid and host plant interact.